Lysosomes in T Cell Immunity and Aging - Jin, Jun; Zhang, Huimin; Weyand, Cornelia M.; Goronzy, Jorg J. (Frontiers in Aging, 2021)
Lysosomes were initially recognized as degradation centers that regulate digestion and recycling of cellular waste. More recent studies document that the lysosome is an important signaling hub that regulates cell metabolism. Our knowledge of the role of lysosomes in immunity is mostly derived from innate immune cells, especially lysosomal degradation-specialized cells such as macrophages and dendritic cells. Their function in adaptive immunity is less understood. However, with the recent emphasis on metabolic regulation of T cell differentiation, lysosomes are entering center stage in T cell immunology. In this review, we will focus on the role of lysosomes in adaptive immunity and discuss recent findings on lysosomal regulation of T cell immune responses and lysosomal dysfunction in T cell aging.